Neurocognitive and autonomic signatures of performance under motivational stress: An integrated psychophysiological analysis of reward and punishment in shooting performance - Cheng, M.-Y.; Wang, K.-P.; Hung, T.-M.; Lu, C.; Oh, H.; Tan, Y. Y.; Hatfield, B. (Scandinavian Journal of Medicine & Science in Sports, 2026)
Motivational framing - such as reward and punishment - critically shapes performance under pressure, yet the underlying neurocognitive and autonomic mechanisms remain unclear. Guided by the cognitive-affective-motor (CAM) model and psychomotor efficiency theory (PET), this study examined how motivational context modulates brain-body dynamics during high-pressure precision performance. Using a within-subject design, elite marksmen performed a simulated shooting task under reward, punishment, and neutral conditions. Neurophysiological markers were assessed across four domains: affective regulation (frontal alpha asymmetry [FAA], eyeblink startle [EBS]), cognitive control (feedback-related negativity [fERN], frontal midline theta), motor readiness (sensorimotor rhythm [SMR], fronto-temporal coherence), and autonomic flexibility (heart rate variability [HRV]). Reward framing elicited a coordinated brain-body state marked by elevated SMR and HRV, greater left-frontal activation, and reduced fERN and coherence-supporting focus, emotional control, and movement stability. Punishment elicited defensive arousal, heightened error sensitivity, and disrupted cortical communication, particularly in lower performers. These results demonstrate that motivational incentives recalibrate neurocognitive and autonomic systems, shaping performance resilience or vulnerability. The identified markers represent viable targets for neurofeedback and biofeedback interventions aimed at enhancing resilience, attentional control, and execution in elite sport performance.